Comparing mass balance-based nutrient management planning tools to support crop fertilisation decisions - Octavian P. Chiriac; Zsofia Bakacsi; Béla Pirkó; María-Llanos López; Elena Pareja-Serrano; Gunther Liebhard; Peter Strauss; Barbora Jachymova; Josef Kraza; José A. Gómez; Javier Montoliu; Gema Guzmán; et al. (Nutrient Cycling in Agroecosystems, 2026)
Nutrient management plan (NMP) tools aim to enhance crop production while minimising environmental harm from over-fertilisation by aligning applications with crop demands and with soil and atmospheric conditions. The characteristics of 14 widely used NMP tools from nine countries (Austria, Bulgaria, China, Czech Republic, Hungary, Italy, New Zealand, Spain, and United Kingdom) were compared. All tools employed a mass balance approach at the field and seasonal scales. To evaluate the tools, matrices of the presence/absence of 24 desirable characteristics, 22 nutrient cycle processes and sources, and 38 required input data were compiled. To compare the NMPs, cumulative scores were calculated for each category evaluated. Additionally, two theoretical case studies compared fertiliser recommendations for winter wheat in arable and livestock farming systems. Cluster analysis classified the 14 tools into six clusters, reflecting distinct levels of complexity, usability, adaptability, and interoperability. The number of input data required was strongly and positively correlated with the number of nitrogen (N) processes and sources considered, confirming that input demand reflects tool sophistication. More comprehensive tools tended to recommend lower N application rates in the livestock system, suggesting that simpler tools overestimated N requirements by omitting key processes. However, practical usability characteristics did not determine different recommendations. While N recommendations were broadly aligned with national guidelines, P and K recommendations showed considerably higher variability reflecting the lack of harmonised guidelines for these macronutrients.